(untitled) (Jurnal Ekonomi dan Kebijakan Pembangunan, 2021)
There are current debates regarding the effect of financial inclusion on income inequality. The effect of financial inclusion on income inequality might be conditional to several other factors. This study aims to investigate the effect of financial inclusion on income inequality conditional to financial structure. This research used Indonesia’s 33 provinces yearly data from 2010 to 2020. Analysis method that was used in this study was static panel data model. The result showed that financial inclusion and financial structure does not significantly affect income inequality. However, for provinces with high HDI, financial inclusion and financial structure demonstrate significant and negative effect on income inequality. Policies on financial inclusion to solve the problem of income inequality needs to consider characteristic of each region, especially human resource quality.